PENERAPAN KEBEBASAN PERS OLEH WARTAWAN DI KOTA MEDAN - Satia Satia (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
ABSTRACT The development of mass media that in such the rapid make competition between each media become tight. Every media has ambition to be the past the lead pack and of the week on wednesday announced an event. So that the issue of media throw easily to the people so that continue to the development of the community wanted to follow the news. Journalist profession is the field of journalistic fewer and fewer people. Is the process of journalistic, engineering and the science of the collection, of writing, and the expected publication of editing news. Freedom of the press and the freedom of the press is the right granted by constitutional or protection laws relating to the media and materials published as more firmly than spread, printing and publishing a newspaper, magazine, a book or in other materials in the absence of intervening or treatment censor of the government . Keywords: mass media , reporters and freedom of the press